Differences In Knowledge And Attitudes Of Seventh Grade Adolescent Girls About Personal Hygiene During Menstruation Before And After Being Given Video Media Counseling - Ni Putu Desika Nadia Anjeli; Ni Ketut Somoyani; Gusti Ayu Eka Utarini (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Personal hygiene during menstruation is one of the important things that everygirls must know and to avoid interference with the reproductive organs. The purpose of this research to see that differences in knowledge and attitudes of seventh grade adolescent girls about personal hygiene during menstruation before and after gave video media counseling at One South Kuta Junior High School. This study used pre-eksperimental design with a one group pretest-postest research design with probability sampling. The sample of this study is 55 adolescent girls from seventh grade. Analysis techniques used paired t-test and wilcoxon test. The results of the study for the average pretest on knowledge was 78.45 and the average posttest on attitude after got video media counseling was 94.18, while for the average pretest on attitude was 73.82 and the average posttest on attitude after getting video media counseling was 79.47. The results on wilocoxon obtained p value = 0.000 <0.05 these results indicate that there is a significant difference in knowledge and attitude before and after being gave video media counseling about personal hygiene adolescent girls. Schools and health workers are expected to work together to provide health counseling related to personal hygiene.